2008
DOI: 10.1007/s11172-008-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of C-adducts of 1,4-diazinium salts with dicarbonyl compounds into polycyclic systems

Abstract: C Adducts of 5 (het)aryl 2,3 dicyano 1 pyrazinium salts containing a residue of a 1,3 dicarbo nyl compound at position 6 can be involved in the cyclization with hydrazine hydrate giving rise to pyrazino[2,3 c]pyridazines along with the expected pyrazole derivatives. The reactions of the same σ H adducts with hydroxylamine unexpectedly afforded triazacyclopenta[a]indene derivatives. The crystallographic data on the three dimensional structures of new polycyclic compounds were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The absorption maxima of the four dyes 21a-d in the solid state were red-shifted (Table 2) by 2-5 nm compared with those for the corresponding dyes in CH 3CN. For D-π-A fluorescent dyes, in general, the redshifts of absorption or fluorescence maxima by changing from solution to the solid state are quite common and explained in terms of the formation of intermolecular π-π interactions 27 or continuous intermolecular hydrogen bonding 28 in the crystalline state leading to delocalization of excitons or eximers.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
“…The absorption maxima of the four dyes 21a-d in the solid state were red-shifted (Table 2) by 2-5 nm compared with those for the corresponding dyes in CH 3CN. For D-π-A fluorescent dyes, in general, the redshifts of absorption or fluorescence maxima by changing from solution to the solid state are quite common and explained in terms of the formation of intermolecular π-π interactions 27 or continuous intermolecular hydrogen bonding 28 in the crystalline state leading to delocalization of excitons or eximers.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
“…1, 2 The main path ways of their transformations include dissociation into the starting compounds, vicarious or oxidative aromatiza tion, 1-3 and non oxidative transformations into other cy clic systems, as recently shown for a number of 2,3 di cyanopyrazines (Scheme 1). [4][5][6][7][8] The goal of the present work was to further study the properties of O and C adducts 2. We found that reflux of σ H adducts 3a,b and 4 (compounds 3a,b were prepared from 5 (het)aryl 2,3 dicyano 1 ethylpyrazinium salts 1 and the acetylacetonate anion; compound 4 is the adduct of salt 1 and water) in o xylene for 2 h gives tetraaza phenanthrenes 5a,b (Scheme 2, Table 1).…”
mentioning
confidence: 99%
“…[4][5][6][7] The piperazine ring assumes the boat conformation. The endocyclic C-N bonds (N(1)-C(2) and N(5)-C(6)) and one methyl group, as well as the protons at the sp 3 hybrid ized C(16) and C(17) atoms of the dihydropyrazine rings, occupy axial positions, while the second methyl group and the C-C bonds of the dihydropyrazine rings (C(17)-C(18) and C(16)-C(15)) occupy equatorial po sitions.…”
mentioning
confidence: 99%